Characterization, In Silico Antimalarial, Antiinflammatory, Antioxidant, and ADMET Assessment of Neonauclea excelsa Merr. - Musa, Neksumi; Dahiru, Mubarak Muhammad; Badgal, Enoch Buba (Sciences of Pharmacy, 2024)
In our study, we identified the phytoconstituents and carried out antimalarial, anti-inflammatory, antioxidant, and ADMET assessments of Neonauclea excelsa. The phytochemicals were detected and quantified followed by identification via GC-MS. The antimalaria, anti-inflammatory, and antioxidant assessments were done by molecular docking (MD) and molecular dynamics simulation (MDS) while ADMET by ADMET predictions. Saponins (27.33% ±1.20) and terpenes (8.33% ±0.73) were detected while alkaloids, steroids, glycosides, and flavonoids were absent. Exactly 29 compounds were identified with squalene being the most abundant (32.41%). Compound II exhibited the lowest BA (-6.4 kcal/mol) and Ki (20.12 µM), interacting with dihydrofolate reductase-thymidylate synthase. IV exhibited the lowest respective BA and Ki interacting with Plasmodium falciparum hexose transporter protein 1 (-6.2 kcal/mol and 28.20 µM), cyclo-oxygenase-2 (-7.2 kcal/mol and 5.21 µM), and myeloperoxidase (-7.4 kcal/mol and 3.71 µM). Compound VII had the lowest respective BA and Ki interacting with inducible nitric oxide synthase (-8.0 kcal/mol and 1.35 µM), xanthine oxidase (-7.2 kcal/mol and 5.21 µM), and cytochrome p450 21A2 (-7.0 kcal/mol and 7.30 µM). The MDS showed various cluster mobilities and residue fluctuations up to 5.26, 2.96, 5.10, 3.51, 5.02, 4.65, and 6.18 Å for dihydrofolate reductase-thymidylate synthase, Plasmodium falciparum hexose transporter protein 1, inducible nitric oxide synthase (INOS), cyclo-oxygenase-2 (COX2), xanthine oxidase (XO), cytochrome p450 21A2, and myeloperoxidase, respectively. Additionally, these compounds demonstrated good pharmacological properties with minimal toxicity. Conclusively, the identified compounds might be significant contributors to the antimalarial, anti-inflammatory, and antioxidant activity of N. excelsa and are good sources of novel antimalarial, anti-inflammatory, and antioxidant drugs.